Neurogenesis Is Reduced at 48 h in the Subventricular Zone Independent of Cell Death in a Piglet Model of Perinatal Hypoxia-Ischemia - Alonso-Alconada, Daniel; Gressens, Pierre; Golay, Xavier; Robertson, Nicola J. (Frontiers in Pediatrics, 2022)
Cellular and tissue damage triggered after hypoxia-ischemia (HI) can be generalized and affect the neurogenic niches present in the central nervous system. As neuroregeneration may be critical for optimizing functional recovery in neonatal encephalopathy, the goal of the present work was to investigate the neurogenic response to HI in the neurogenic niche of the subventricular zone (SVZ) in the neonatal piglet. A total of 13 large white male piglets aged <24 hours were randomized in two groups: i) HI group (n=7), animals submitted to transient cerebral HI and resuscitation and ii) Control group (n=6), non-HI animals. At 48h, piglets were euthanized and the SVZ, together with the SVZ-surrounding regions caudate and periventricular white matter, were analyzed for histology using hematoxylin-eosin staining and immunohistochemistry evaluating the presence of cleaved caspase 3 and TUNEL positive cells, together with the cell proliferation/neurogenesis markers Ki67 (cell proliferation), GFAP (neural stem cells processes), Sox2 (neural stem/progenitor cells) and doublecortin (DCX, a marker of immature migrating neuroblasts). Hypoxic-ischemic piglets showed a decrease in cellularity in the SVZ independent of cell death, together with decreased length of neural stem cells processes, neuroblast chains area, DCX immunoreactivity, and lower number of Ki67+ and Ki67+Sox2+ cells, thus suggesting that a reduction in both cell proliferation and neurogenesis in the SVZ of the neonatal piglet. This could compromise the replacement of the lost neurons and the achievement of global repair, so treatments designed to maintain or even augment neurogenesis after neonatal HI might contribute to functional recovery.